Molecular characterization of pathogenic Aeromonas jandaei bacteria isolated from cultured walking catfish (Clarias sp.) - DINI SISWANI MULIA; NOERHALIZA RAHMAN DWI; SUWARSITO SUWARSITO; BOBY MUSLIMIN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Mulia DS, Dwi NR, Suwarsito, Muslimin B. 2024. Molecular characterization of pathogenic Aeromonas jandaei bacteria isolated from cultured walking catfish (Clarias sp.). Biodiversitas 25: 1185-1193. Aeromonas spp. is pathogenic bacteria capable of causing fish disease, including walking catfish (Clarias sp.). In bacteria, virulence genes play a significant role in determining pathogenicity, while resistance genes influence resistivity. Therefore, this study aimed to determine molecular characterization of pathogenic Aeromonas jandaei bacteria isolated from walking catfish. The purposive sampling method was used to obtain diseased walking catfish from aquaculture ponds in Banyumas District, Central Java Province, Indonesia. The identification of bacteria was molecularly carried out based on 16S rDNA, followed by the detection of virulence genes on aer/haem, alt, ast, flaA, lafA, and fstA, as well as resistance genes on tet-A, strA-strB, and qnrA. The results of molecular analysis showed that three isolates from Singasari, namely BmSL-02, BmSL-04, and BmSL-07, were closely related to A. jandaei strain CDC0787-80 with a similarity rate and query coverage of 99.86% and 99%, respectively. Meanwhile, isolates from Cikawung, including BmCL-02, BmCL-05, and BmCL-07 were closely related to A. jandaei strain ATCC 49568. A total of six A. jandaei isolates had aer/haem virulence genes while alt, ast, and fstA were not found. BmSL-04 and BmCL-07 isolates had flaA gene, while four isolates including BmSL-02, BmSL-04, BmSL-07, and BmCL-07 had lafA gene. Additionally, BmCL-05 had tetA resistance gene, while the strA-strB and qnrA genes were not detected in all isolates. A. jandaei isolates were resistant to bacitracin, tetracycline, and gentamycin, but BmSL-04, BmSL-07, BmCL-02, and BmCL-05 were sensitive to chloramphenicol. This study provided valuable information on molecular characteristics of A. jandaei, serving as guidance in effective control and monitoring of isolates from Indonesia, specifically Banyumas, Central Java.